Non-additive effect of the DNA methylation inhibitor, 5-Aza-dC, and glass as a culture surface on osteogenic differentiation. Issue 12 (December 2022) - Alghfeli, Latifa; Parambath, Divyasree; Tag Eldeen, Loaa A.; El-Serafi, Ibrahim; El-Serafi, Ahmed T.
Abstract: The clinical need for bone regenerative solutions is expanding with increasing life expectancy and escalating incidence of accidents. Several strategies are being investigated to enhance the osteogenic differentiation of stem cells. We previously reported two different approaches for this purpose, in monolayer and three-dimensional cell culture. The first approach was based on pretreating cells with 5-Aza-dC, a DNA methylation inhibitor, before the applying the differentiation media. The second approach was based on culturing cells on a glass surface during differentiation. In this study, we investigated the potential effect of combining both methods. Our results suggested that both approaches were associated with decreasing global DNA methylation levels. Cells cultured as a monolayer on glass surface showed enhancement in alkaline phosphatase activity at day 10, while 5-Aza-dC pretreatment enhanced the activity at day 5, irrespective of the culture surface. In three-dimensional pellet culture, 5-Aza-dC pretreatment enhanced osteogenesis through Runx-2 and TGF-β1 upregulation while the glass surface induced Osterix . Furthermore, pellets cultured on glass showed upregulation of a group of miRNAs, including pro-osteogenesis miR- 20a and miR -148b and anti-osteogenesis miR -125b, miR -31, miR -138, and miR -133a. Interestingly, 5-Aza-dC was not associated with a change of miRNAs in cells cultured on tissue culture plastic but reverted the upregulated miRNAs on the glass to the basal level. This study confirms the two approaches for enhancing osteogenic differentiation and contradicts their combination. Abstract : Stem cells; Regenerative medicine; Osteogenesis; Bone; miRNA; Glass; Biomaterial; Epigenetic modifier; Epigenetics.